Influences of bull age and season on sperm motility, sperm concentration, and ejaculate volume of Ongole Grade cattle in Singosari National Artificial Insemination Center - Suyadi, S.; Purwantara, B.; Furqon, A.; Septian, W. A.; Novianti, I.; Nursita, I. W.; Nugraha, C. D.; Putri, R. F.; Pratiwi, H.; Herwiyati, E. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
Ongole Grade cattle is one of local cattle in Indonesia.This study was aimed to analyze the effect of bull age and season on semen quality of Ongole Grade cattles macroscopically (sperm motility, and sperm concentration) and microscopically (semen ejaculate volume) to support the policy and management on improvement of semen production. Data were collected from 533 ejaculates of 10 bulls aged 3, 4, and 5 yr at Singosari National Artificial Insemination Center(SNAIC). The 4-year-old bulls hadhighestsperm motiliy and semen ejaculate volume. The lowest ejaculate volume was reported in Ongole Gradecattlesaged 3 yr. Sperm motility and concentrationweresignificantly higher (P<0.01) in wet season than dry season. In conclusion, the bull age and season should be considered by Singosari National Artificial Insemination Centerwhen collecting the semen, especially on bulls aged 3 yr old and in dry season.